Operations in Space, Operations in Memory: An analysis of Welcome Park, designed by Venturi, Scott Brown & Rauch in Philadelphia - Atique, Fernando (2015)
This paper presents a study of the Welcome Park, a kind of memorial designed by the US Office of Robert Venturi, Denise Scott-Brown and John Rauch. Located in a former private area, the lot was turned into a square and was incorporated to the American Independence Park, in the city of Philadelphia. The site allows us to show important conceptions of project, contrasting with the general scheme adopted by the US Park. In this way, the paper shows that intending to celebrate the William Penn, the founder of Philadelphia, the architects developed an important reflexion concerning the conceptions of memory and history in that city.